KESIAPAN GURU DALAM MENGIMPLENTASIKAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA(P5) PADA KURIKULUM MERDEKA DI SEKOLAH DASAR - Lia Rahayu; Adelia Junita; Findi Rinta Fiani; Muhammad Jaya Adi Putra; Mutia Yulita Sari (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to analyze the readiness of teachers in implementing the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum at SD IT Al-Fityah. P5 is a project-based learning approach that aims to shape students' character in accordance with Pancasila values. The research method used is qualitative, with data collection techniques through semi-structured interviews and documentation studies. Five teachers selected based on certain criteria were interviewed to obtain data related to understanding, preparation, challenges, and collaboration in the implementation of P5. The results showed that teachers' understanding of P5 varied, and many teachers faced challenges such as a lack of training and clear guidance. However, commitment and collaboration between teachers and support from schools and parents are important factors in supporting the implementation of P5. This study concludes that teachers' readiness to implement P5 needs to be improved, especially through more intensive training and continuous mentoring, so that the goals of P5 in forming students with Pancasila character can be optimally achieved.